Who really 'created'? Psalm 19 and evolutionary psychology in dialogue - Viviers, H. (Old Testament Essays, 2008)
The beauty and awe that the natural world evokes lead humans intuitively to believe in an all powerful creator as is convincingly exemplified by Psalm 19. The author allows both nature and law to communicate elatedly about this god, who is believed to exist objectively. This ease with which human beings conceptualize counterintuitive beings ('gods'), has lately been confirmed by Evolutionary Psychology as well. The 'Theory of Mind' mental tool especially, plays a primary role in this regard. To 'think up' a god(s), responsible for the world and its functioning, comes naturally and intuitively. Evolutionary Psychology, however, differs from Psalm 19, namely therein that 'god' is a subjective construct. Bringing Darwinian evolution into the conversation, the problem of the 'existence of god' becomes even more critical, as evolution does not need a creator god. But god(s) persists. In reaction to the personal 'god' of theism and the no-god of atheism, seeking the 'godly' (atheism) becomes quite attractive.
free